Perbedaan Tingkat Kecemasan antara Siswa RSBI (Rintisan Sekolah Bertaraf Internasional) dan Akselerasi di SMA NEGERI 1 SURAKARTA - Putri, Della Kusumaning; Fanani, Muhammad; Murti, Bhisma (Nexus Kedokteran Klinik, 2012)
Background: The anxiety at the students approaching teenagers age is the manifestation of the transition of emotional, morality, and relationship in family. A study was performed to the division of acceleration and RSBI classes in SMA Negeri 1 Surakarta creates the Difference of Anxiety Level between them because there is a psychological pressure constituting the high achievement demand. Methods: This was an analytic observational research with cross sectional approach. The subjects were the students of SMA Negeri 1 Surakarta. The sampling technique was using purposive sampling. The research data obtained by two different questionaire, the L-MMPI questionnaire, and Taylor Manifest of Anxiety Scale questionnaire (T-MAS). This study analysed statistically with Chi SquareÂ  test. Results: 58 samples were consisted of 26 accelerationâs students and 32 RSBIâs students. Based on analyzed data, there were differences of anxiety level at the students of acceleration and RSBI (Rintisan Sekolah Bertaraf Internasional) programs in SMA Negeri 1 Surakarta (p=0.036;OR 0.30). Conclusions: The differences of anxiety level were statistically significant between accelerationâs students and RSBIâs students (p=0.036). Anxiety level for students in acceleration was 0.3 times higher than the students in RSBI program. Keywords: anxiety, acceleration, RSBI.Â